Embracing researcher subjectivity in phenomenological research: A response to Ann Scott - Finlay, Linda (European Journal for Qualitative Research in Psychotherapy, 2009)
All researchers experience times of confusion and uncertainty and risk getting lost in the complex ambiguity of the research journey. We are inevitably challenged by the research process especially when it comes to trying to disentangle ourselves from our participants given the relational context of the research. The research process both profoundly affects and is affected by the researchers. Research can never be a ‘value- free’ zone - researcher subjectivity is always present. There is a clear need for researchers to be reflexive and to critically interrogate the impact of their subjectivity on the research and of the research on them. This process mirrors our work as psychotherapists where we reflect on clients’ stories while analysing our own responses and the dynamics of the evolving relationship between ourselves and our client. In this paper I examine some of the ways that phenomenological and heuristic researchers in particular manage – and even embrace - their subjectivity. Two processes are especially involved: the epoché and reflexivity. Both these concepts are briefly described here to act as a guide for researchers wishing to explicitly work with their subjectivity. I also offer practical research examples to illustrate how the theory can be applied in practice.